Phytoremediation of salinized soils by the application of vinasse - Silva, Raquel Zanholo da; Conte, Ana Maria (Scientia Agraria Paranaensis, 2017)
Areas cultivated with sugarcane, where continuous vinasse application is used, tend to have serious physical, biological and mainly chemical problems due to the excess nutritional load that is transmitted by this byproduct. In order to evaluate the chemical quality of the soil after phytoremediation, an experiment was carried out in protected cultivation in the area of Experimental Farm Eduardo Meneghel Rando, of campus Luiz Meneghel of the State University of Northern Paraná, in the city of Bandeirantes, Paraná State, Brazil, and evaluated by the factorial design at 0, 30, 45 and 60 days after emergence of the crops and the secondary plot of the six treatments with three replicates: T1- Crotalaria spectabilis, T2- Mucuna deeringiana, T3- Pennisetum americanum, T4- Zea mays, T5- Canavalia ensiformis and T6- Phaseolus vulgaris. The experiment was carried out in pots with a capacity of 12.6 L, filled with soil collected at two depths 0-20 and 20-40 cm, at the USIBAN-Açúcar and Álcool Bandeirantes S/A industry, in the city of Bandeirantes, and initially evaluated for their routine chemical characteristics. Through destructive analysis the soil was evaluated from 0-20 cm and 20-40 cm, for routine analysis of soil chemical parameters at 30, 45 and 60 days after emergence (DAE) of the crops. The results allowed conclude that the cultivation of millet was the treatment that best remedied potassium up to 45 DAE in soils salinized by the application of vinasse.